Avaliação do potencial fisiológico, condicionamento e armazenamento de sementes de melão - Medeiros, Maria Aparecida de (2012)
This paper aimed to study procedures for conducting tests of controlled deterioration (moisture content 20, 22 and 24% at 45 ° C for 24 hours), accelerated aging (periods 48, 72 and 96 hours at 38 and 41 ° C ) and electrical conductivity (temperature 25 ° C, volumes 50 and 75 mL of water, 25 and 50 seeds and soaking periods of 4, 6, 8, 12 and 24 hours), checking for their efficiency in the presence of different levels vigor seed lots of melon (Cucumis melo L.) as well as analyze the effect of priming during storage, listing the standard germination, first count germination and seedling emergence. Comprised of four experiments using two hybrids, Imperial and Gaucho, each represented by four seed lots. In the first experiment we selected the procedures for conducting tests of controlled deterioration, accelerated aging (with and without saturated NaCl solution) and electrical conductivity. In the second experiment the procedures considered most promising for each test were examined, of the first experiment. In the third considered the most promising for each test, of the first experiment. In the third experiment, we repeated the best results of the second experiment, by way of confirmation, including only the germination and first count. The fourth experiment consisted of priming, drying and storage of seeds during (0, 30, 60 and 90 days) under controlled conditions (18-20 ° C and 45% RH). The results indicate that the controlled deterioration test (20% / 24h/45 ° C) for accelerated aging and non-saturated NaCl solution (41 ° C/72h) and electrical conductivity (25/sementes/50mL/25 ° C for six hours soaking ), were efficient to detect vigor differences among seed lots of melon. It was noticed that the storage of seeds under controlled conditions, allows the maintenance of the beneficial effects of conditioning